Spontaneous, Voluntary, and Affective Behaviours in Rat Models of Pathological Pain - Draxler, Peter; Moen, Aurora; Galek, Karolina; Boghos, Ani; Ramazanova, Dariga; Sandkühler, Jürgen (Frontiers in Pain Research, 2021)
In pain patients affective and motivational reactions as well as impairment of daily life activities dominate the clinical picture. In contrast, many rodent pain models have been established on the basis of mechanical hypersensitivity testing. Up to today most rodent studies on pain still rely on reflexive withdrawal responses only. This discrepancy has likely contributed to the low predictive power of preclinical pain models for novel therapies. Here, we used a behavioural test array for rats to behaviourally evaluate five aetiologically distinct pain models consisting of inflammatory-, postsurgical-, cephalic-, neuropathic- and chemotherapy-induced pain. We assessed paralleling clinical expressions and comorbidities of chronic pain with an array of behavioural tests to assess anxiety, social interaction, distress, depression, and voluntary/spontaneous behaviours. Pharmacological treatment of the distinct pain conditions was performed with pathology-specific and clinically efficacious analgesics as gabapentin, sumatriptan, naproxen, and codeine. We found that rats differed in their manifestation of symptoms depending on the pain model and that pathology-specific analgesics also reduced the associated behavioural parameters. Based on all behavioural test performed, we screened for tests that can discriminate experimental groups on the basis of reflexive as well as non-sensory, affective parameters. Together, we propose a set of non-evoked behaviours with a comparable predictive power to mechanical threshold testing for each pain model.